Spray Characteristics at Preheating Temperatur of Diesel-Biodiesel-Gasoline Fuel Blend - Arifin, Moch Miftahul; Ilminnafik, Nasrul; Kustanto, Muh. Nurkoyim; Triono, Agus (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
Technological developments in diesel engines require improvements to the fuel injection system to meet the criteria for economical, high-power and efficient combustion and meet environmental regulatory standards. One method that has a lot of interest is changing the characteristics of the fuel, with the aim of producing optimal combustion. Spray characteristics have a big role in determining the quality of combustion in diesel engines. A good spray can improve the quality of fuel atomization and the homogeneity of the air-fuel mixture in the combustion chamber so that it can produce good engine performance and low emissions. This study aims to determine the effect of a diesel-biodiesel (Calophyllum inophyllum)-gasoline blendandfuel heating on the spray characteristics. The research was conducted with variations in composition (B0, B100, B30, B30G5 and B30G10) and fuel heating (40, 60, 80, and 100 °C). Fuel injected atapressure of 17 MPa in to a pressure chamber of 3 bar. The spray formed was recorded with a high-speed camera of 480 fps (resolution 224x168 pixel). In B100 biodiesel, the highest viscosity and density cause high spray tip penetration, small spray angle, and high spray velocity. The addition of diesel oil, gasoline, and heating fuel reduces the viscosity and density so that the spray tip penetration decreases, the spray angle increases and the velocity of spray decreases.